Impacto antrópico en la estructura y calidad del paisaje en la vía Cuenca-Girón-Pasaje - Chicaiza Cuzco, Solange Lizbeth (My University, 2025)
This research aims to evaluate the anthropic impact on the structure and quality of the landscape at five strategic points along the Cuenca–Girón–Pasaje road, located in the provinces of Azuay and El Oro, Ecuador. This road section crosses sensitive ecosystems such as páramo, montane forest, and tropical dry forest, which have been drastically transformed by urban expansion, road infrastructure, and extractive activities. The study adopted a mixed methodology that integrated qualitative and quantitative approaches, analyzing variables such as landscape fragmentation, remaining vegetation cover, ecological connectivity, and land use. The results show that the sampling points located in areas of greater human intervention (PDM3 and PDM5) present higher levels of degradation, with fragmented landscapes, low connectivity, and a predominance of agricultural and urban activities. In contrast, PDM4 located in the páramo area shows a better state of conservation, with minimal anthropic presence. The study concludes that anthropic intervention has dramatically transformed the Andean and coastal ecosystems in the area, compromising biodiversity and ecosystem services. It is recommended to implement comprehensive landscape management measures that articulate ecological conservation with sustainable development at the local level.
La presente investigación tiene como objetivo evaluar el impacto antrópico sobre la estructura y calidad del paisaje en cinco puntos estratégicos de la vía Cuenca-Girón-Pasaje, ubicada en las provincias de Azuay y El Oro, Ecuador. Este tramo vial atraviesa ecosistemas sensibles como Páramo, Bosque Montano y Bosque Seco Tropical, los cuales han sido transformados drásticamente por la expansión urbana, la infraestructural vial y las actividades extractivas. El estudio adopto una metodología mixta, integrando enfoques cualitativos y cuantitativos, analizando variables como fragmentación del paisaje, cobertura vegetal remanente, conectividad ecológica y uso del suelo. Los resultados demuestran que los puntos de muestreo ubicados en las zonas de mayor intervención humana (PDM3 y PDM5) presentan mayores niveles de degradación, con paisajes fragmentados, baja conectividad y predominio de actividades agrícolas y urbanas. En contraste el PDM4 localizado en la zona de Páramos evidencia un mejor estado de conservación, con mínima presencia antrópica. Se concluye que la intervención antrópica ha transformado drásticamente los ecosistemas andinos y costeros de la zona, comprometiendo la biodiversidad y los servicios ecosistémicos. Se recomienda implementar medidas de manejo integral del paisaje que articulen la conservación ecológica con el desarrollo sostenible a nivel local.
Keywords: Impacto antrópico; Paisaje; Conectividad ecológica; Uso del suelo; Conservación; Desarrollo sostenible.